ANALISIS CEMARAN BAKTERI COLIFORM PADA SAUS TOMAT JAJANAN BAKSO TUSUK YANG BEREDAR DI MANADO - Mansauda, Karlah L. R. (PHARMACON, 2014)
The tomato sauce is one of the processed foods that are often presented as a complement to a wide variety of foods that many consumers demand. But in the daily life the cleanliness of tomato sauce is often overlooked. This research aims to analyze the microbial contamination of 12 tomato sauces of bakso tusuk snack in the city of Manado such as examining total plate count, coliform bacteria and Escherichia coli bacterial identification. This type of research is Observational. The results showed that of the 12 samples of tomato sauce all sample are positive bacterial contaminated, coliform bacteria contaminated and Escherichia coli is contained in all sample. Testing of microbial contamination showed that tomato sauce samples did not meet predetermined requirements in SNI 01-3546-2004 and Regulation of the Food and Drug Administration of The Republic of Indonesia number HK.00.06.1.52.401. Key words : Tomato sauce, Total Plate Count, Coliform, Escherichia coli